High Voltage Stress and Equipotential Mapping Using FEM Method (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to study the voltage stress and the equipotential mapping for a sample of 33kV porcelain insulator, which is used widely in the Sudanese national grid. The available modeling and analysis package COMSOL multi-physics was used, and a limited number of experiments using the high voltage laboratory facility at University of Khartoum was attempted to compare the simulation and experimental results. The simulation predicts that 30 kV/cm ionization (for air at standard conditions) occurs at about 105 kV, while experimentally ionization started as a visible corona discharge at about 101 kV peak .
Keywords: Comosol/M; Dirichlet boundary condition; Neumann boundary condition; Finite element method; Equipotential Mapping.